2011
DOI: 10.1029/2010wr009890
|View full text |Cite
|
Sign up to set email alerts
|

A water isotope approach to assessing moisture recycling in the island‐based precipitation of Taiwan: A case study in the western Pacific

Abstract: [1] This study employs a dual-isotope (d 18 O and dD), three-end-member linear mixing model to semiquantitatively assess vapor contributions of advection, transpiration, and evaporation to precipitation, and to compare the extent of moisture recycling (including transpiration and evaporation) among areas of various topographic types in Taiwan, an island located in the western Pacific. The three topographic types examined are the mountainous regions, foothill regions (as represented by two reservoir stations), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 49 publications
0
40
0
Order By: Relevance
“…Considering the great fluctuations of isotopic compositions in xylem water as well as the similarity of xylem and precipitation isotope ratios, in this study the weighted mean precipitation isotopes values were used for δ tr , as suggested by Peng et al . [].…”
Section: Methodsmentioning
confidence: 99%
“…Considering the great fluctuations of isotopic compositions in xylem water as well as the similarity of xylem and precipitation isotope ratios, in this study the weighted mean precipitation isotopes values were used for δ tr , as suggested by Peng et al . [].…”
Section: Methodsmentioning
confidence: 99%
“…In most practical cases, it is estimated from other parameters. Peng et al (2011) suggested a relationship between initial precipitation and d A (Eq. (16)).…”
Section: Estimates Of Evaporation Rates Of Infiltrating Water Throughmentioning
confidence: 99%
“…In contrast to evaporation, transpiration and condensation practically do not affect the d-excess (Gat, 2005). Therefore, the d-excess in precipitation that includes recycled moisture can be used to estimate the evaporation component of the recycled fraction (Froehlich et al, 2008;Peng et al, 2011).…”
Section: Introductionmentioning
confidence: 98%